Genetics, climate and phylogeography : understanding the Hiberno-Iberian distribution of Daboecia cantabrica (Huds). K. Koch and Erica mackaiana Bab. (Ericaceae) - Eftonga, Sarah Rosarine Pene (Trinity College (Dublin, Ireland). Department of Botany, 2013)
Dahoecia cantahrica (Huds.) K. Koch and Erica mackaiana Bab. are two ericaceous species whose disjunct distribution in Europe is best described as Hiberno-Iberian. Both species have their origins in the Atlantic coastal areas of the Iberian peninsula, are absent from Britain, and are found only in certain areas of the west of Ireland. How and when the current populations of these species became established in Ireland has been a question of debate for over 150 years. To gain an understanding of the processes and events that have shaped this unusual distribution a combined approach of molecular analysis and species distribution modelling was carried out.
Keywords: Botany, Ph.D.; Ph.D. Trinity College Dublin.